Crescimento relativo de Macrobrachium acanthurus (Wiegmann, 1836) (Crustacea, Decapoda, Palaemonidae) - Valenti, Wagner Cotroni [UNESP]; Lobão, Vera Lúcia; Mello, Jeanette T. Cardoso de (Sociedade Brasileira de Zoologia, 1989)
In this paper, the relative growth of Macrobrachium acanthurus (Wiegmann, 1836) (Crustacea, Decapoda, Palaemonidae), is presented; the cephalothorax length/abdominal length, telson length/abdominal length and abdominal length/total length relashionships were determined. The adjusted equations showed a isometric growth pattern. There are no changes in these relationships during the animals growth that may be significant in the maximization of the meat's profit.